Quantitative study of bioinformatics analysis on glioma: a bibliometric analysis - Yang, Xiaobing; Man, Dulegeqi; Zhao, Peng; Li, Xingang (Frontiers in Oncology, 2023)
Background: The bioinformatics analysis on glioma has been a hot point recently. The purpose of this study was to provide an overview of the research in this field using a bibliometric method.Methods: The Web of Science Core Collection (WOSCC) database was used to search for literature related to the bioinformatics analysis of gliomas. Countries, institutions, authors, references, and keywords were analyzed using VOSviewer, CiteSpace, and Microsoft Excel software.Result: China was the most productive country, while the USA was the most cited.Capital Medical University had the largest number of publications and citations.Institutions tend to collaborate more with other institutions in their countries rather than foreign ones. The most productive and most cited author was Jiang Tao. Two citation paths were identified, with literature in basic research journals often cited in clinical journals. Immune-related vocabularies appeared frequently in recent studies.Conclusion: Glioma bioinformatics analyses spanned a wide range of fields. The international communication in this field urgently needs to be strengthened. Glioma bioinformatics approaches are developing from basic research to clinical applications.Recently, immune-related research has become a focus.